Analisis Keuntungan Maksimum Penjualan Sandal dan Sepatu Toko Faa’iz Collection - Tiur Malasari Siregar; Jesika Ramadani Ritonga; Meilafayza Nasha; Kristiana Simbolon; Andri Pratama Pencawan (Universitas Negeri Surabaya, 2023)
This study analyzes the maximum profit of FAA'IZ Collection business, a newly pioneering business, has problems determining sales targets to achieve maximum profit and the right price to be determined on each product sold. The research aims to evaluate whether the sales quantity has been achieved or not, analyze it, the amount of sales quantity, and determine the right price for products that provide maximum profit. The research subjects in this study are FAA'IZ Collection business actors in Medan, North Sumatra and the object of research is sales sandals, savilo sandals, eiger, Yumeida rubber shoes, comin shoes, and ikayni sandals. The results of the analysis state that (1) In January 2023, FAA'IZ Collection can achieve maximum profit only from the sale of comin shoes (2) In February 2023, FAA'IZ Collection is able to achieve maximum profit only from the sale of eiger and comin shoes (3) In January and February 2023, FAA'IZ Collection has not been able to achieve maximum profit only from the sale of comin shoes. Prevent maximum losses from sales of Savilo sandals and Irayni sandals (4) There are minimum products that need to be checkedby the FAA'IZ Collection to achieve maximum profits for sale sandal products 6,087, eiger 51,000, and comin shoes 56,250.